Analisis Manajemen Lingkungan Terhadap Kejadian Malaria di Kecamatan Biak Timur Kabupaten Biak-Numfor Papua. - Rumbiak, Helmin; Setiani, Onny; Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2006)
ABSTRACT Background: Malaria is one of diseases caused by parasite protozoa from genus of Plasmodium. Malaria in Indonesia is one of main problems of health. Biak regency is one of regency at Papua that have high-rate of clinical malaria is 48,677 cases per year by mean of Annual Malaria Incidence (AMI) is 395, 88% per year. Bosnik Community Health CentreWork Region is having the most high of High Incidence Area (HIA) in Biak-Numfor, by mean rate of AMI is 395,88%, this rate is so far over the national mean rate 31,090/00. This thesis was aimed to analyze the implementation of environmental management for the incidence of malaria in Malaria Endemic Area at Bosnik Community Health Centre, Biak-Numfor regency. Methods: this research was an observational research with a cross- sectional approach.The number of sample was 100 people. Data were obtained from The Meteorology and Geophysics Station Corporation of Class 1st Frans Kaisiepo Biak. Results: The results of the research showed that the implementation of environmental Â management in Community Health Centre area of Bosnik during last five years (2001-2005) did not carry on continually, The environment and socio economic condition in Bosnik Community Health Centre area has influence the risk of malaria incidence. Conclusion : Environmental management such as spraying and environmental sanitation for malaria control should be taken continually to decrease the malaria incidence in Biak. Keywords: Environmental Management, Vector Control, Malaria Incidence